2016
DOI: 10.1021/acs.analchem.5b04653
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Sea DuraFET: A Pressure Tolerant pH Sensor Designed for Global Sensor Networks

Abstract: Increasing atmospheric carbon dioxide is driving a long-term decrease in ocean pH which is superimposed on daily to seasonal variability. These changes impact ecosystem processes, and they serve as a record of ecosystem metabolism. However, the temporal variability in pH is observed at only a few locations in the ocean because a ship is required to support pH observations of sufficient precision and accuracy. This paper describes a pressure tolerant Ion Sensitive Field Effect Transistor pH sensor that is based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
137
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(142 citation statements)
references
References 36 publications
1
137
0
Order By: Relevance
“…Johnson et al, 2016;. In addition, empirical algorithms for alkalinity must be used to estimate pCO 2 from float-based pH [Carter et al 2016;Williams et al 2016].…”
Section: !mentioning
confidence: 99%
“…Johnson et al, 2016;. In addition, empirical algorithms for alkalinity must be used to estimate pCO 2 from float-based pH [Carter et al 2016;Williams et al 2016].…”
Section: !mentioning
confidence: 99%
“…Temperature and salinity were obtained from the Sea-Bird CTD sensor on the ship rosette sampler, and the seawater equilibrium constants presented by Mehrbach et al (1973) were used as refitted by Dickson and Millero (1987), which has been recommended by previous studies (e.g. the CARINA data synthesis project) for the Mediterranean Sea (Álvarez et al, 2014;Key et al, 2010). The sulfate constant described by Dickson (1990) and the parameterisation of total borate presented by Uppström (1974) were used.…”
Section: Ship-based Measurementsmentioning
confidence: 99%
“…It is known that temperature and pressure have an effect on E * (strong linear relationship) and that the Nernst slope is a function of temperature. Studies have also shown that it is possible for ISFET sensors to experience some form of hysteresis as a result of changing T and pressure Bresnahan et al, 2014;Johnson et al, 2016). The first step in correcting pH g aimed to reduce the measured extent of variability to within the measured limits of pH s .…”
Section: Isfet Ph Validationmentioning
confidence: 99%
See 2 more Smart Citations